Two-pore channels for integrative Ca2+ signaling - Zhu, M; Evans, A; Ma, J; Parrington, J; Galione, A (2010)
Two-pore channels (TPCs) are related to voltage-gated Ca2+ and Na+ channels. They most likely work as dimers with each of the two TPC protein subunits containing two pore-forming domains. Recent studies suggest that TPCs are expressed on the membranes of endosomes and lysosomes where they form receptors for nicotinic acid adenine dinucleotide phosphate (NAADP), the most potent Ca2+ mobilizing messenger inside cells. Upon activation by NAADP, Ca2+ release from endolysosomal stores through TPCs triggers cytoplasmic Ca2+ signals. Because of discrete localizations of these acidic vesicles and their small, albeit variable, sizes, the Ca2+ signals from endolysosomes are local and, perhaps, represent unique elementary Ca2+ events. These localized signals can be converted into regenerative global Ca2+ waves by triggering Ca2+-induced Ca2+ release from endoplasmic reticulum. We will discuss the implications of these findings and the significance of TPCs in integrative Ca2+ signaling in animal cells. © 2010 Landes Bioscience.